Open innovation practices in strategic partnerships of cloud computing providers - Cândido, Ana Clara (2017)
The open innovation states that companies can and must use the available resources outside their boundaries. This combination of ideas aligned to the internal and external technologies are crucial to reach a leadership position. The present study aims to identify the practices of open innovation along the partnerships between providers of Cloud Computing. Social Network Analysis were used in the research. Data was collected through questionnaires secondary sources. The companies were asked to identify their strategic partnerships and to identify and characterize the practices of Open Innovation they actually use. Of the 26 strategic partnerships mentioned, only 11 were characterized as practices of the Open Innovation.